Professional short films with Autodesk 3DS MAX - Neuhahn, Chris (Charles River Media, 2006)
Animated short films are a unique form of storytelling that allows you to bring your characters and ideas to life. If you've ever considered telling your own visual story but haven't been sure of how to get started, you've come to the right place. Written by experienced animators and producers, this book provides practical and insightful ideas into how to use AutodeskÂđ 3ds MaxÂđ for your own short film productions. It is about using the tools in 3ds Max to create short films that are on par with feature films. It teaches 3ds Max users everything about animated fi lm creation from coming up with a story, storyboards, character rigging, and animation to lighting, lip syncing, facial animation, and editing. The book provides a unique look at film production through the use of an actual film, Vacant Planet: A Curious Bit of Scrap as a case study. This case study is evaluated through a series of tutorials in you will create using methods similar scenes to those found in Vacant Planet. Using the insights and techniques highlighted in the case study, along with the files on the companion DVD-ROM, you will work through the entire process and be ready to turn your own stories into animated tales. The book does assume prior 3ds Max knowledge and is written for users who want to turn their skills toward creating short films. This is a must-have book for 3ds max users, film artists, and character animators who want to use Max's animation power to the fullest!